Perlindungan Ideal Atas Hak Dipilih Warga Negara yang Berprofesi Sebagai Pegawai Negeri Sipil - Wahid, La Ode Haerul Saleh (Fakultas Syariah INSURI Ponorogo, 2023)
This research was conducted to find out how to limit the right to be elected by citizens who work as Civil Servants and how should the protection of the right to be elected by citizens who work as Civil Servants. This research uses a normative approach and is descriptive in nature. Methods of data collection using literature study and document analysis. Data analysis was performed using qualitative analysis methods. The results of the study show (1) restrictions on the right to be elected for citizens who work as Civil Servants are excessive restrictions and not ideal because in order to exercise the right to be elected, he must lose his right to work without any guarantee of getting a new job, and (2) Protection The ideal for the right to be elected by civil servants is by changing the time of resignation from civil servant status, where civil servants who have just registered as candidates in elections or regional elections simply temporarily resign from their civil servant status, and only resign permanently after the election process is complete. Arrangements like this have implications for the realization of restrictions on political rights that do not endanger the essence of the rights themselves, where restrictions can still be made but there is maximum protection for the right to vote for civil servants. Having the option to submit an active application again if not elected will be a differentiator and a sign that the state provides maximum human rights protection for every citizen, including those who work as civil servants.